Addressing complexity in design: a systemic model of creativity and guidelines for tools and methods. Issue 1 (3rd April 2017) - Bila-Deroussy, Pathum; Bouchard, Carole; Diakite Kaba, Saran
Abstract: The aim of this paper is to show how the systemic approach makes it possible to redefine creativity; it highlights new ways to stimulate it in complex industrial contexts. A model was constructed from a state-of-the-art review categorized according to three conceptual scales (environment, individual, and object) using the systemic approach. It highlights three fundamental interactions (perceptual, cognitive, and social) that synthesize the mechanisms of creativity as a whole. From this model, three guidelines were proposed: the use of analogical tools to stimulate perceptual interactions, the use of a language based on visual forms to stimulate cognitive interactions, and the use of a cyclical process alternating individual, social and expert creativity to stimulate social interactions. Deployed together as an embedded method, we argue that these guidelines improve creative performance in complex contexts by focusing on interactions that stimulate the overall creativity system. We conclude with an implementation of this method in our industrial context (a car manufacturer), and test the guidelines in the context of real industrial projects.